The impact of fashion brand sustainability on consumer purchasing decisions - Doroteja Mandarić; Anica Hunjet; Dijana Vuković (Journal of Risk and Financial Management, 2022)
The focus of this confirmatory research was on consumer attitudes towards the sustainability of fashion brands and how these attitudes influence their purchasing decisions. The aim was to explore if the gap between attitudes and purchasing behaviour was present within Croatian consumers to the same extent as previous research has shown. A survey was conducted of 263 respondents with purchasing power to examine their perception, awareness of, and attitudes towards sustainability and eco-fashion as consumers. The data collected were analysed using descriptive statistics and correlation analysis. The results suggest that participants have a positive attitude towards the sustainability of fashion brands. Moreover, a positive correlation was found between the importance of fashion brand sustainability and consumers' decisions to buy sustainable clothing products. However, the sustainability of a fashion brand or product is among the least important factors in their purchasing decision. This could mean that their positive attitude may not necessarily be reflected in actual purchasing behaviour, which is consistent with previous research. The results of this study provide a framework for a greater understanding of the various factors that may influence consumer behaviour, such as the sustainability of a fashion brand or product, potentially facilitating the development of relevant strategies in the fashion industry and changing the way fashion works and is perceived in the future.
Keywords: 650; consumer awareness; consumer behaviour; consumer responsibility; eco-fashion; sustainable business; sustainable consumer behaviour; sustainable fashion